Effects of crude extracellular protein and crude intracellular polysaccharides of Vibrio alginolyticus on the growth, energy metabolism regulation and WSSV resistance of Litopenaeus vannamei. (31st August 2018) - Shan, Hong‐Wei; Yu, Peng; Liu, Kuan; Ma, Shen; Yu, Ming‐Chao
Abstract: This study aimed to investigate the effects of adding crude extracts of the extracellular protein (Ex‐Pro) and intracellular polysaccharides (In‐Poly) of Vibrio alginolyticus to diets, at a dosage of 10 g/kg, on the growth, energy metabolism and WSSV (White Spot Syndrome Virus) resistance of Litopenaeus vannamei (initial weight, 0.88 ± 0.04 g/shrimp). Growth and survival rate were not significantly affected by the crude extracts ( p  >   0.05). Shrimp fed Ex‐Pro crude extracts showed higher succinate dehydrogenase (SDH) activity in the hepatopancreas and muscle but lower lactate dehydrogenase (LDH) activity in the muscle ( p  <   0.05). The activities of hexokinase (HK), pyruvate kinase (PK), LDH and SDH in the hepatopancreas and the activity of SDH in the muscle were significantly increased by feeding In‐Poly crude extracts ( p  <   0.05). In contrast, the content of fatty acid synthase (FAS) in the muscle was significantly reduced by the crude extracts ( p  <   0.05). The contents of glucose and triglyceride and the activity of the electron transport system in the hepatopancreas were significantly increased by the crude extracts ( p  <   0.05), and the WSSV resistance of the shrimp was increased. These results indicated that the Ex‐Pro and In‐Poly crude extracts of V. alginolyticus could affect energy metabolism, and there was a correlation between WSSV resistance and energy metabolism in L. vannamei .